2022
DOI: 10.3390/j5030025
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Psychological Well-Being among Physicians and Nurses in Makkah’s Major Hospitals

Abstract: Background: Physicians and nurses experience poor psychological well-being relative to other employees in healthcare fields. This study aimed to evaluate the psychological well-being among physicians and nurses in Makkah’s major hospitals. Methods: In this cross-sectional study, 460 physicians and nurses from seven major hospitals in Makkah were recruited to investigate their psychological well-being using the General Health Questionnaire-12 (GHQ-12) based on social dysfunction, anxiety, and confidence loss. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The well-being of the nurses seemed better; this indicates that nurses are aware of an individual’s overall, psychological, interpersonal, and environmental state, each of which interacts with the others and has a different level of significance and influence. In several studies, the authors indicated that high degrees of psychological anguish are prevalent among Saudi Arabian nurses, which threatens their well-being [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The well-being of the nurses seemed better; this indicates that nurses are aware of an individual’s overall, psychological, interpersonal, and environmental state, each of which interacts with the others and has a different level of significance and influence. In several studies, the authors indicated that high degrees of psychological anguish are prevalent among Saudi Arabian nurses, which threatens their well-being [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%